Evaluasi Pengaruh Motivasi Kerja Terhadap Kinerja Pekerja Pada Proyek Peningkatan Jalan Pakalu – Soddange Kabupaten Maros - Darmiati, Darmiati; Abduh, Natsir; Prasandi, Savitri (Program Studi Teknik Sipil Universitas Bosowa, 2025)
Motivation is a solution in increasing the morale of skilled workers in construction in order to maximize worker performance to achieve project goals. The aim of this research is to determine the variables Work Relations (X1), Work Environment (X2), Work Benefits (X3), and Worker Wages (X4) which influence Worker Performance (Y) by knowing the motivation variables and the results. The type of research used is quantitative research methods. The analysis technique used is SPSS. The population in the research is all workers from the Pakalu-Soddange Road Improvement Project, Maros Regency, totaling 31 people. From the percentage point analysis of all respondents, all Work Motivation Variables (X) are Work Relationship Variables (X1) with a percentage result of 49.0%, Work Environment Variables (X2) of 45.2%, Work Benefits Variables (X3) of 38 .7%, Worker Wage Variable (X4) with a percentage result of 64.3% has an effect on Worker Performance (Y). The variable that most dominantly influences work motivation on the performance of workers at the Pakalu-Soddange Road Improvement Project, Maros Regency is the Worker Wage Variable (X4) with a percentage result of 64.3%..